SPCalc: A web-based calculator for sample size and power calculations in micro-array studies - Qiu, Weiliang (Biomedical Informatics Publishing Group, 2006)
Calculation of the appropriate sample size in planning microarray studies is important because sample collection can be expensive and time-consuming. Sample-size calculation is also a challenging issue for microarray studies because the number of genes is far larger than the number of samples so that traditional methods of sample-size calculation cannot be directly applied. To help investigators answer the question of how many samples are needed in their microarray studies, we developed a user-friendly web-based calculator, SPCalc, for calculating sample size and power for a variety of commonly used experimental designs, including completely randomized treatmentcontrol design, matched-pairs design, multiple-treatment design having an isolated treatment effect, and randomized block design. AVAILABILITY: The web-based calculator SPCalc is publicly available at http://www.biostat.harvard.edu /people/faculty/mltlee/webfront-r.html